Aetiology of Diarrhoea and Virulence Properties of Diarrhoeagenic Escherichia coli among Patients and Healthy Subjects in Southeast Nigeria (Journal of Health, Population and Nutrition, 2010)
Diarrhoeal diseases are one of the most important causes of illness and death all over the world. In Nigeria,the aetiology of diarrhoeagenic bacteria and the virulence of various Escherichia coli pathotypes have notbeen well-studied because most currently-published data were from the southwestern axis of the country.In total, 520 stool samples were collected from infants, young children, and other age-groups with acutediarrhoeal diseases in Enugu and Onitsha, southeastern Nigeria. Stool samples were collected from 250apparently-healthy individuals, with similar age distribution and locality, who were considered controlsubjects. The stool samples were screened for diarrhea-causing bacterial agents. E. coli strains were isolatedfrom both the groups and were examined by polymerase chain reaction (PCR) for 16 virulence genes. Ofthe 520 stool samples in the diarrhoea group, 119 (44.74%) were E. coli. Fifty (49.02%) were enteropathogenicE. coli (EPEC), 22 (21.57%) were enterotoxigenic E. coli (ETEC) while 7.84% was enteroaggregativeE. coli (EAEC). Sex had no effect on the distribution of diarrhoeagenic bacteria, except for EIEC. The E. colistrains isolated from the diarrhoea and healthy asymptomatic age-matched control groups examined byPCR for 16 virulence genes indicate that the detection of EAEC, ETEC, EPEC, and EIEC was significantlyassociated with diarrhoea (p=0.0002). The study confirmed that several bacterial pathogens, such as E. coli,play an important role in the aetiology of acute diarrhoea in southeastern Nigeria. A routine surveillance,especially for diarrhoeagenic E. coli, would be useful in identifying outbreaks and help identify the potentialreservoirs and transmission routes.Key words: Diarrhoea; Escherichia coli; Virulence; NigeriaDOI: 10.3329/jhpn.v28i3.5551J HEALTH POPUL NUTR 2010 Jun;28(3):245-252